FORMS AND METHODS OF PROFESSIONAL TRAINING OF FUTURE TEACHERS: KEY TRENDS, EXPERIENCE IN THE CONDITIONS OF CLUSTER APPROACH (Education in the 21st Century, 2023)
The article reveals the development trends of continuing teacher education in the Republic of Belarus, which act as the basis for the selection of forms, methods and technologies for the training of teachers. The experience of cluster interaction in the industry is described, which allows for continuity and continuity at all its levels: from specialized pedagogical classes to adult education institutions. The results of an empirical study on the use of forms, methods and means of professional training of teachers in educational institutions of the educational-scientific-innovative cluster of continuing teacher education are presented.